2010
DOI: 10.1080/00224490902954323
|View full text |Cite
|
Sign up to set email alerts
|

Power, Sex, and Rape Myth Acceptance: Testing Two Models of Rape Proclivity

Abstract: Power and sex are thought to be important factors associated with sexual aggression. The goal of this study was to offer a dual-process model to determine how both an implicit power-sex association and explicit power-sex beliefs contribute to rape myth acceptance and rape proclivity. In Study 1, an explicit measure of power-sex beliefs was developed using a participant sample of 131 college students (54% female; age: M = 20.2 years, SD = 3.5 years). In Study 2, 108 male college students (age: M = 19.1 years, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 45 publications
3
58
0
3
Order By: Relevance
“…This interpretation suggests that adolescent rape may be a strategy for displaying normative masculinity. A growing body of research has found that believing in popular myths about the role of victims and perpetrators in rape increases tendencies toward rape (Bohner et al, 1998;Chapleau & Oswald, 2010). In light of gender norms that portray "real men" as having uncontrollable sexual desires, some youth who perpetrate sexual assault may not see their actions as problematic.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation suggests that adolescent rape may be a strategy for displaying normative masculinity. A growing body of research has found that believing in popular myths about the role of victims and perpetrators in rape increases tendencies toward rape (Bohner et al, 1998;Chapleau & Oswald, 2010). In light of gender norms that portray "real men" as having uncontrollable sexual desires, some youth who perpetrate sexual assault may not see their actions as problematic.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between rape myth acceptance and rape proclivity was examined in a two part study using two models of rape proclivity (Chapleau & Oswald, 2010). The first part of the study investigated the phenomenon of power and sex using 131 college students (54.2% women; mean age = 20.2, S = 3.5) from a Midwestern Catholic University.…”
Section: Later Studiesmentioning
confidence: 99%
“…No rape myth acceptance feedback condition participants' R scales did not have any answers underlined nor were there any references to previous respondents' choices. Participants' rape proclivity was assessed using five acquaintance-rape scenarios utilized in previously reviewed studies (Bohner, Jarvis et al, 2005;Chapleau & Oswald, 2010;Chiroro et al, 2004).…”
Section: Later Studiesmentioning
confidence: 99%
“…Furthermore, researchers have found that greater endorsement of rape myths is associated with greater proclivities to commit sexual violence, to not believe victims, and to offer less support for victims (Bohner, Siebler, & Schmelcher, 2006;Chapleau & Oswald, 2010;Franiuk, Seefelt, & Vandello, 2008). Bohner et al (2006) also found that perceived social norms interacted with individuals' own acceptance of rape myths.…”
Section: Consequences Of Rape Mythsmentioning
confidence: 99%